Sustainable Development and Public Policy Revitalization - Kristian, Indra (The International Journal of Education Management and Sociology, 2022)
Sustainable development appears as a new concept or approach, as a correction to development policies or strategies adopted after World War II until the 1980s which were deemed to have failed to achieve the goal, namely creating people's welfare for today's society and humanity in the future. will come. This concept was born from the rise of awareness that economic development has exceeded the carrying capacity of the natural environment, so that this sustainability is questioned. This paper uses a systematic literature review approach. In facing the trends and future of public administration, especially the effects of democratization, the environment, globalization, and the development of information technology, there must be anticipation accompanied by appropriate efforts and steps in the study and practice of public administration. Without these efforts, it is certain that public administration in Indonesia will be left behind, unable to solve administrative problems, and in turn the Indonesian nation will not be able to compete with other nations in the world.